2019
DOI: 10.3171/2018.3.jns172846
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and opinions of US neurosurgical residents toward research and scholarship: a national survey

Abstract: OBJECTIVE The analysis of resident research productivity in neurosurgery has gained significant recent interest. Resident scholarly output affects departmental productivity, recruitment of future residents, and likelihood of future research careers. To maintain and improve opportunities for resident research, the authors evaluated factors that affect resident attitudes toward neurosurgical research on a national level. METHODS An online survey was distributed to all US neurosurgical residents. Questions assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Most American residency programs encourage their residents to pursue research activities. Most American residents have a year or more of protected research time (31). Similarly, 45.0% of residents in Latin America are enrolled in a program with protected research time (32).…”
Section: Researchmentioning
confidence: 99%
“…Most American residency programs encourage their residents to pursue research activities. Most American residents have a year or more of protected research time (31). Similarly, 45.0% of residents in Latin America are enrolled in a program with protected research time (32).…”
Section: Researchmentioning
confidence: 99%
“…Em Portugal, os estudos sobre a formação especializada em Neurocirurgia são escassos, impedindo a identificação das referidas dissemelhanças formativas existentes a nível nacional e internacional, nomeadamente quanto ao número de horas de trabalho, ao género dos médicos internos, à publicação de artigos e à carreira académica. [10][11][12][13][14][15][16][17][18] É opinião dos autores que a satisfação dos médicos internos pode ser influenciada por vários fatores previamente identificados em estudos internacionais, como características e organização dos serviços, carga horária, distribuição de tarefas e oportunidades formativas (teóricas e práticas) disponibilizadas.…”
Section: Enquadramento E Formulação Do Estudounclassified
“…11 A study by Karsy et al investigated resident attitudes toward research and scholarship, noting that scholarly output affects the likelihood of pursuing a research career in the future. 12 The investigators found that mentorship and research exposure were important for residents to achieve high levels of scholarly productivity and thus likely influential in determining their future career trajectories. Though so far uninvestigated in neurosurgery, the influence of job availability on trainees' future career trajectory is likely also important and merits attention in future research.…”
Section: Prior Researchmentioning
confidence: 99%